Habituation of Kaheman Rice in Building Students' Character (Case Study at SMPN 2 Campaka) - Suharyanto H Soro; Nana Herdiana Abdul Rahman; Feby Filga Cantika; Siti Nuraeni (Civiliza Publishing, Indonesia., 2026)
This research is based on the challenges of moral degradation and empathy crises among the younger generation due to digital disruption, as well as the gap between character education policies and practical realities in the field that still tend to be cognitive. This study aims to analyze the implementation of the